2012
DOI: 10.1002/j.1532-2149.2012.00226.x
|View full text |Cite
|
Sign up to set email alerts
|

Intensity of chronic pain modifies postural control in low back patients

Abstract: Body balance measurements seemed to confirm the hypothesized role of the altered executive function in the CLBP problems, with a further support from pain assessment that indicated central sensitization. Patients with higher self-reported pain level displayed deficit in the postural adaptability to environmental challenge and lower level of postural automaticity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 44 publications
6
35
2
Order By: Relevance
“…In a separate analysis we did not find a difference in sway frequency and regularity between subjects with a VAS score of 1-2, and subjects without LBP (results not reported). In the second study (Sipko & Kuczyń ski, 2012), changing the stance condition from solid surface to foam increased sway regularity in subjects with low levels of LBP, while regularity was not affected in subjects with high levels of LBP. The authors conclude in line with our findings, that subjects with high levels of LBP have less cognitive investment in balance control, relying on lower levels of control when standing on foam (Sipko & Kuczyń ski, 2012).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In a separate analysis we did not find a difference in sway frequency and regularity between subjects with a VAS score of 1-2, and subjects without LBP (results not reported). In the second study (Sipko & Kuczyń ski, 2012), changing the stance condition from solid surface to foam increased sway regularity in subjects with low levels of LBP, while regularity was not affected in subjects with high levels of LBP. The authors conclude in line with our findings, that subjects with high levels of LBP have less cognitive investment in balance control, relying on lower levels of control when standing on foam (Sipko & Kuczyń ski, 2012).…”
Section: Discussionmentioning
confidence: 83%
“…While standing on foam requires some effort to maintain balance, subjects with LBP may solve this not by increasing attention and supraspinal control of the postural task, but prefer lower level control due to pain distraction (i.e., increasing stiffness through co-contraction or by increasing feedback gains). To our knowledge two studies have been conducted before, in which subjects with LBP were compared to healthy controls with respect to the regularity of sway when standing on foam (Mazaheri, Salavati, Negahban, Sanjari, & Parnianpour, 2010;Sipko & Kuczyń ski, 2012). In the first study, no significant differences were found (Mazaheri et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…However, there is growing evidence of a central origin in chronic back pain (Flor et al, 1997;Sipko and Kuczyński, 2013), relating to altered postural adjustment strategies (Moseley and Hodges, 2005;Popa et al, 2007;Tsao et al, 2008) and not to the descending motor drive (Hodges, 2001). Recently, it was proposed that sensory feedback from the painful muscle is re-weighted, whereby more reliable signals coming from non-painful regions are given preference (Brumagne et al, 2000(Brumagne et al, , 2004Popa et al, 2007;Claeys et al, 2011).…”
Section: Balance and Postural Assessmentsmentioning
confidence: 99%
“…12 Chronic pain has been shown to modify postural control in patients with low back pain, leading to a deficit in postural adaptability and requiring increased cognitive investment to maintain balance. 13 In addition, there is growing evidence for recurrent balance dysfunction related to migraine headache. 14 Chronic pain has also long been recognized to adversely affect brain function.…”
Section: Methodsmentioning
confidence: 99%